Neutrophil Activation: Influence of Antimony Tolerant and Susceptible Clinical Strains of L. (V.) panamensis and Meglumine Antimoniate - Fernández, Olga Lucía; Ramírez, Lady Giovanna; Díaz-Varela, Míriam; Tacchini-Cottier, Fabienne; Saravia, Nancy Gore (Frontiers in Cellular and Infection Microbiology, 2021)
Emerging evidence indicates that innate host response contributes to the therapeutic effect of antimicrobial medications. Recent studies have shown that Leishmania parasites derived by in vitro selection for resistance to pentavalent antimony (SbV) as meglumine antimoniate (MA) modulate the activation of neutrophils. However, whether modulation of neutrophil activation extends to natural resistance to this antileishmanial drug has not been established. We have evaluated the influence of clinical strains of L. (V.) panamensis having intrinsic tolerance/resistance to SbV, on the inflammatory response of neutrophils during ex vivo exposure to MA. Accordingly, neutrophils obtained from healthy donors were infected with clinical strains that are sensitive (n = 10) or intrinsically tolerant/resistant to SbV (n = 10) and exposed to a concentration approximating the maximal plasma concentration (Cmax) of SbV (32 µg/ml). The activation profile of neutrophils was evaluated as the expression of the surface membrane markers CD66b, CD18, and CD62L by flow cytometry, measurement of reactive oxygen species (ROS) by luminometry, and NET formation using Picogreen to measure dsDNA release and quantification of NETs by confocal microscopy. These parameters of activation were analyzed in relation with parasite susceptibility to SbV and exposure to MA. Here, we show that clinical strains presenting intrinsic tolerance/resistance to SbV induced significantly lower ROS production compared to drug-sensitive clinical strains, both in the presence and in the absence of MA. Likewise, analyses of surface membrane activation markers revealed significantly higher expression of CD62L on cells infected with intrinsically SbV tolerant/resistant L. (V.) panamensis than cells infected with drug-sensitive strains. Expression of other activation markers (CD18 and CD66b) and NET formation were similar for neutrophils infected with SbV sensitive and tolerant clinical strains under the conditions evaluated. Exposure to MA broadly impacted the activation of neutrophils, diminishing NET formation and the expression of CD62L, while augmenting ROS production and CD66b expression, independently of the parasite susceptibility phenotype. These results demonstrated that activation of human neutrophils ex vivo is differentially modulated by infection with clinical strains of L. (V.) panamensis having intrinsic tolerance/resistance to SbV compared to sensitive strains, and by exposure to antimonial drug.